Hawgent Dynamic Mathematics Software to Teach Line and Angle - Xiangjie Zhang; Ying Zhou; Tommy Tanu Wijaya (JNPM (Jurnal Nasional Pendidikan Matematika), 2020)
Abstract. This research aims to use Hawgent dynamic mathematics software to create a learning media on lines and angles based on students' weaknesses and difficulties when studying the material using traditional methods. This research is development research using the ADDIE model. Instruments in the form of validation sheets and practicality. The results show that learning media using Hawgent dynamic mathematics software can explain basic concepts in the material of lines and angles. Implementation in learning and teacher and student responses show that Hawgent learning media positively affects learning the concept of lines and angles. Students in the experimental class are more active when explaining the material on lines and angles using Hawgent dynamic mathematics software. So that this learning media can help students in teaching and learning activities in class.Keywords: Hawgent dynamic mathematics software, Line and angle, ICT.